Guerrilla warfare in Katanga: the Sanga rebellion of the 1890s and its suppression. (29th July 2019) - Macola, Giacomo; Hogan, Jack
ABSTRACT: This article discusses the origins and development of the Sanga insurgency of the 1890s with a view to demonstrating that, contrary to commonly held stereotypes, pre-colonial warfare was neither simple nor unchanging. Its tactics, it is argued here, repay the sort of close analysis commonly reserved for other typologies and theatres of war. The Yeke, against whose exploitative system of rule the Sanga and their allies rose up in 1891, survived the onslaught by entering into a strategic alliance with Lofoi, a newly established station of the Congo Free State, and its limited contingent of regular Force Publique troops. An in-depth examination of the joint Yeke-Force Publique counterinsurgency campaign leads to the conclusion that the novelty of the 'small wars' that accompanied the Scramble for Africa should not be overstated. In southern Katanga and, by implication, elsewhere, these confrontations were shaped by processes of mutual borrowing in which African military practices and even political aims were not necessarily subordinate to European ones.